2020
DOI: 10.1001/jamainternmed.2019.7087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Common Prescribing Cascade of Calcium Channel Blockers and Diuretics in Older Adults With Hypertension

Abstract: IMPORTANCE Calcium channel blockers (CCBs) are commonly prescribed agents for hypertension that can cause peripheral edema. A prescribing cascade occurs when the edema is misinterpreted as a new medical condition and a diuretic is subsequently prescribed to treat the edema. The extent to which this prescribing cascade occurs at a population level is not well understood.OBJECTIVE To measure the association between being newly dispensed a CCB and subsequent dispensing of a loop diuretic in older adults with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 36 publications
3
96
0
2
Order By: Relevance
“…The look back period of 1 year was chosen as it was unlikely treatment for an existing condition would remain untreated for more than a year under routine circumstances. A 1 year look back period has been used in previous analyses of prescribing cascades [ 42 ] but there have been look-back periods as short as 6 months in employ [ 9 ]. Once confirmed that the second treatment was not used in the year preceding the inciting medication the individual was followed forward from the first dispensing of the inciting medication to identify an overlapping prescription with the second treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The look back period of 1 year was chosen as it was unlikely treatment for an existing condition would remain untreated for more than a year under routine circumstances. A 1 year look back period has been used in previous analyses of prescribing cascades [ 42 ] but there have been look-back periods as short as 6 months in employ [ 9 ]. Once confirmed that the second treatment was not used in the year preceding the inciting medication the individual was followed forward from the first dispensing of the inciting medication to identify an overlapping prescription with the second treatment.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 14 Our materials focused on the calcium channel blocker–diuretic (CCB–diuretic) prescribing cascade. 3 , 15 This prescribing cascade occurs when a healthcare provider misinterprets swelling of the legs and feet (edema) secondary to a CCB as a new medical condition and prescribes a diuretic to treat the swelling, which has the potential to lead to additional adverse effects ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a cohort study, this particular cascade occurred in 9.5% of older adults who were newly prescribed a calcium channel blocker (Appendix 1, available at www.cmaj.ca/lookup/doi/10.1503/cmaj.201564/tab-related-content ). 2 …”
Section: A Prescribing Cascade Refers To the Sequence Of Events In Whmentioning
confidence: 99%